Teacher professional development for managing antisocial behaviors: a qualitative study to highlight status, limitations and challenges in educational institutions in the metropolis city of Pakistan - Siddiqui, Sohni; Kazmi, Anjum Bano; Kamran, Mahwish (Frontiers in Education, 2023)
A community cannot avoid the frustrating problem of antisocial behavior, which consists of actions that violate traditions or standards. To deal with the antisocial behavior and aggression in children, a variety of techniques and interventions have been proposed and applied throughout the world. Teachers can overcome antisocial behavior in educational institutions through professional development programs. In Pakistan, there are few studies that focus on teachers' professional development in behavior management, which should be investigated. A qualitative research study examined teacher professional development courses aimed at improving classroom management skills and controlling antisocial behaviors by collecting information from instructors. This approach was taken because this study aims to identify teacher educators' experiences related to antisocial and aggression control training in the school setting. In addition, the limitations and challenges associated with such development programs are revealed through semi-structured interviews. Researchers reported major challenges related to such trainings include resistance and unwillingness of school authorities and teachers to participate in such trainings, as well as lack of resources and finances. To ensure that teacher training is effective and leads to the development of teacher skills and improvement of student behavior, researchers recommend implementing evidence-based intervention programs with ongoing monitoring by a trained teacher specialist. It is also recommended that curricula be standardized and in-service training results be empirically verified.